Relationship of Intracellular Calcium and Oxygen Radicals to Cisplatin-Related Renal Cell Injury - Yoshiko Kawai; Takafumi Nakao; Naoshi Kunimura; Yuka Kohda; Munekazu Gemba (Elsevier, 2006)
Abstract.: We investigated the involvement of reactive oxygen species (ROS) and intracellular calcium in nephrotoxicity related to an antitumor agent, cisplatin. In this study, we employed cultured renal epithelial cells (LLC-PK1). Cisplatin at 500 µM significantly increased the production of ROS 5 h and caused cell injury. This agent significantly increased the intracellular calcium level ([Ca2+]i) in a dose-dependent manner 1 h or more after exposure. DPPD (N,N'-diphenyl-p-phenylenediamine), an antioxidant, inhibited a cisplatin-related increase in active oxygen production and cell injury but did not inhibit an early increase in the [Ca2+]i level. An intracellular calcium-chelating compound BAPTA-AM (1,2-bis(O-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid tetra(acetoxymethyl) ester) inhibited an increase in ROS production and cell injury induced by cisplatin. Furthermore, BAPTA-AM suppressed the rise of [Ca2+]i level in 1 h after exposure; however, an extracellular calcium chelator EGTA and a calcium antagonist nicardipine did not inhibit the rise in [Ca2+]i level in the early phase. An NADPH oxidase inhibitor inhibited a cisplatin-related increase in ROS production and cell disorder. These results suggest that cisplatin-related calcium release from the site of intracellular calcium storage in the early phase causes oxidative stress in renal tubular epithelial cells. Cisplatin may increase the intracellular production of ROS via NADPH oxidase. Keywords:: cisplatin, nephrotoxicity, reactive oxygen species, intracellular calcium, renal epithelial cell